ANALYSIS OF AQUAPONIC LETTUCE AND TILEFISH WITH NUTRIENT FILM TECHNIQUE (NFT) SYSTEM AT PT. TANIKOTA - Ayu Atikah Putri; Dini Rochdiani (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
Organic vegetables produced by aquaponic cultivation are exclusive vegetables with many benefits, so don't be surprised if they are more expensive than ordinary vegetables. PT. Tani Kota is one of the companies engaged in agribusiness with aquaponic cultivation techniques with the Nutrient Film Technique (NFT) system. PT. Tanikota has not carried out farming calculations using precise and detailed accounting technology; currently, in calculating costs and income, it is still conventional, not using the software, so it is not known whether farming is efficient. This study aimed to analyze the level of income and the break-even point (BEP) of lettuce and tilapia farming aquaponics with the Nutrient Film Technique (NFT) system. The research method used is a case study at PT. Tanikota. The analysis used in this research is the analysis of farm income and Break-Even Point (BEP). This study indicates that the income from lettuce farming is Rp. 14,958,510,81 and tilapia, which is Rp. 2,752,360.81 per one aquaponic growing season. The break-even point analysis (BEP) results showed that the BEP of lettuce production volume was 85,463 kg and tilapia was 109,230 kg. BEP sales of lettuce are Rp. 4,358,579,630 and tilapia is Rp. 5,734,620.56. This means that the production and sales pass the break-even point, which means that aquaponic lettuce and tilapia farming is profitable or feasible